IoT-ID: Deterministic Device Identity from Hybrid Network Fingerprinting - Letycia, Anna; Assolin, Joner; Kreutz, Diego; Miani, Rodrigo (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
This paper presents IoT-ID, a deterministic fingerprinting system for IoT device identification based on network traffic analysis. By combining passive and active measurements into a canonical multi-layer representation and applying cryptographic hashing, IoT-ID derives stable and reproducible device identities without relying on training data. The integration of application-layer metadata with transport-layer signatures resolves collisions between devices with indistinguishable network stacks, enabling consistent identification across heterogeneous environments. Results confirm the feasibility and effectiveness of deterministic fingerprinting, while highlighting limitations in non-IoT systems due to privacy mechanisms and software homogeneity.